2021
DOI: 10.7717/peerj.10841
|View full text |Cite
|
Sign up to set email alerts
|

The kinematic analysis of the lower limb during topspin forehand loop between different level table tennis athletes

Abstract: Background Topspin is one of the most attacking stroke in table tennis sport. The aim of this research was to investigate the kinematic characteristics of the lower limb (driving leg) during topspin forehand loop in different playing level table tennis athletes. Methods Ten male table tennis athletes performed topspin forehand loop shots with maximal force to hit the ball that was played by a professional table tennis coach. The three-dimensional Vicon motion analysis system was used to capture the kinematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This may contribute to a greater range of weight transfer and thus momentum generation ( He et al, 2020 ; Ball & Best, 2007 ; Zhang et al, 2017 ). Previous studies have reported on the underlying mechanisms of lower limb energy transfer and racket speed ( Zhang et al, 2017 ; He et al, 2021 ; Iino & Kojima, 2009 ). In this study, the chasse step showed significantly greater plantar force than the one step in the 21.06–84.06% process of FP.…”
Section: Discussionmentioning
confidence: 99%
“…This may contribute to a greater range of weight transfer and thus momentum generation ( He et al, 2020 ; Ball & Best, 2007 ; Zhang et al, 2017 ). Previous studies have reported on the underlying mechanisms of lower limb energy transfer and racket speed ( Zhang et al, 2017 ; He et al, 2021 ; Iino & Kojima, 2009 ). In this study, the chasse step showed significantly greater plantar force than the one step in the 21.06–84.06% process of FP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that table tennis is not a majority sport in many countries, about 300 million individuals participate in table tennis [1], of whom at least 40 million are competitive players [2]. As in other sport disciplines [3,4], it is important to know the health status of the athletes, especially in amateur category players who usually cannot count on being monitored by qualified personnel in training sessions and competitions.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the human joint movement on racket movement has always been the main content of biomechanical research on the topspin forehand. The maximum speed of the racket is increased through the human kinetic chain effect, which brings benefits to enhancing the rotation and aggression of the ball [ 5 , 6 , 9 , 23 ]. In general, racket velocity is related to the angular velocity of axial motion of the hip, pelvis, and ankle joints.…”
Section: Resultsmentioning
confidence: 99%
“…The whole-body coordination mechanism is very important in table tennis, and the performance level of the upper limbs is largely determined by the lower limbs [ 4 , 5 ]. In recent years, the important role of lower limb function in table tennis has been widely studied and reported [ 2 , 4 , 6 , 7 , 8 , 9 , 10 , 11 ]. As the origin of the kinetics chain, perfect lower limb movement performance will benefit the velocity of the racket and ball [ 4 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%